2019
DOI: 10.1371/journal.pone.0217355
|View full text |Cite
|
Sign up to set email alerts
|

Novel phthalocyanines activated by dim light for mosquito larva- and cell-inactivation with inference for their potential as broad-spectrum photodynamic insecticides

Abstract: Mosquitoes are significant vectors, responsible for transmitting serious infectious diseases, including the recent epidemics of global significance caused by, for example, Zika, Dengue and Chikungunya viruses. The chemical insecticides in use for mosquito control are toxic and ineffective due to the development of resistance to them. The new approach to reduce mosquito population by releasing genetically modified males to cause female infertility is still under environmental safety evaluation. Photodynamic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…This phenomenon is known as photodynamic inactivation (PDI) and has been explored for decades in the treatment of pathologies and the elimination of microorganisms 11,12 . In the last 5–10 years, a considerable number of studies have demonstrated the PDI action in target insects 10,13–16 . However, its use in the vector control segment is still underestimated due to the lack of research directed to its viability and field application, as well as its impacts on vector biology.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is known as photodynamic inactivation (PDI) and has been explored for decades in the treatment of pathologies and the elimination of microorganisms 11,12 . In the last 5–10 years, a considerable number of studies have demonstrated the PDI action in target insects 10,13–16 . However, its use in the vector control segment is still underestimated due to the lack of research directed to its viability and field application, as well as its impacts on vector biology.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Shiao et al [78] (Entry 11, table 2) evaluated phthalocyanine-derived PSs in A. aegypti mosquito larvae (IPhCl: Aluminum phthalocyanine chloride, PC1-2: aminophthalocyanines; PC3-4: triethylene glycol-substituted Zn(II)phthalocyanines, PC3 .4-3.7: Anilinium Zn-phthalocyanines, PC14: Pyridyloxy Si-phthalocyanine and five porphyrin derivatives as (BPDZM: M-Benziporphodimethene, NCPS: meso tetrakis(p-sulfonatophenyl)N-confused porphyrin tetrasodium. TPPS4: Meso-tetra(4) -sulfonate-phenyl)porphine Tetrasodium, TMAP: meso-tetra(4 n,n,n-trimethylanilinium) porphine tetrachloride, TPPS2: meso-tetraphenylporphine disulphonic acid dihydrochorid), in addition to two PSs of the halogenated fluorescein group (cyanosine and RB) solubilized in different solvents, water, methanol or DMSO.…”
Section: Vdbsmentioning
confidence: 99%
“…Originally discovered as a relatively new anticancer therapeutic technology [ 1 ], photodynamic therapy (PDT) has since evolved and is now used in many therapeutic technologies. For example, it is used against viruses, such as the recently reported antiviral activity against COVID-19 [ 2 ], bacteria [ 3 ], fungi [ 4 ] and parasites [ 5 ], in treating neovascular disease [ 6 ], in environmental sanitation [ 7 ] and pest control [ 8 ], and in many other applications. Besides anticancer applications, photodynamic therapeutic applications against bacteria have defined the knowledge field of antimicrobial photodynamic therapy (aPDT) [ 9 ] and the allied healthcare variant known as photodynamic antimicrobial chemotherapy [ 10 ].…”
Section: Introductionmentioning
confidence: 99%